(untitled) (Cadernos de Sociomuseologia, 2015)
This article aims to establish a theoretical approach between the Social Museology and assumptions of Sociology of Absences, from a preliminary analysis of the concepts of monoculture and ecology conveyed by Portuguese sociologist Boaventura de Souza Santos. Monocultures are responsible for the proliferation of social invisibility and from them, ecologies arise as alternatives to enable the visibility of the silenced social practices and therefore, in forgetting process. The social museology, in turn, has been dedicated to transforming marginalized social processes narratives and museological initiatives that enable reflection and citizen participation from a perspective that includes the museum as a space that can act in the deconstruction of social forms of production of non-existence. Thus, social museology finds fertile ground in the interpretations proposed by the Sociology of Absences to deal with the deconstruction of hegemonic ideas guided to strengthen the non-existence produced by the ignorant image; residual; lower; local and unproductive. Search is here to highlight the possibilities of building a dialogue approaching this sociological interpretation model of social museology scenario highlighting some initiatives of northern Brazil. Key words: social museology; sociology of absences; Brazilian Amazon; museums.